Integrating Assessment with Teaching and Learning Excellence: A Proactive Model - Teresa Flateby; Patricia Gregg (Academic Chairpersons Conference Proceedings, 2020)
Is your department a pocket of excellence? Through interactive case studies and discussion, you will learn how to systematically and proactively connect student learning assessment with curriculum and instructional planning. Walk away with a plan of concrete action steps to get in the pocket to maximize student learning.
Keywords: Assessment; Curriculum; Planning; Improvement; Effectiveness